Gestión directiva administrativa y evaluación del clima organizacional. I.E. N° 5167 "Víctor Raúl Haya de la Torre". Puente Piedra. Lima - Andrade Sosa , Cristina Rita (2023)
Global changes and the development of countries have one of their foundations in the harmony with which the organizational climate is managed with respect to administrative management. The objective of the research was to determine the relationship between administrative management and the organizational climate in Educational Institution N. 5167 “Víctor Raúl Haya de la Torre” in Puente Piedra. Lime. The dimensions planning, organization, direction and control belong to the administrative management variable and the organizational climate variable has as dimensions: communication, motivation, communication and participation. Methodologically we use a quantitative scientific approach, hypothetical deductive method, cross section and ordinal level. Questionnaires with Likert questions validated by 3 expert juries and reliability using Cronbach's Alpha were applied to a sample of 34 teachers and managers. A descriptive correlational design using descriptive and inferential statistics for hypothesis testing using Spearman's Rho, in a sample of 34 we found that according to r=0.412 with a bilateral significance of p= 0.000 we found a highly significant relationship concluding that good management management administrative there is a good organizational climate in the EI under study. The results of the contrast of the general hypothesis were that there is a relationship between Administrative Management and the organizational climate in the UGEL of Puente Piedra.